Fluoxetine and all other SSRIs are 5-HT2B Agonists - Importance for their Therapeutic Effects - Peng, Liang; Gu, Li; Li, Baoman; Hertz, Leif (Current Neuropharmacology, 2014)
Fluoxetine and other serotonin-specific re-uptake inhibitors (SSRIs) are generally thought to owe their therapeutic potency to inhibition of the serotonin transporter (SERT). However, research in our laboratory showed that it affects, with relatively high affinity the 5-HT2B receptor in cultured astrocytes; this finding was confirmed by independent observations showing that fluoxetine loses its ability to elicit SSRI-like responses in behavioral assays in mice in which the 5-HT2B receptor was knocked-out genetically or inhibited pharmacologically. All clinically used SSRIs are approximately equipotent towards 5-HT2B receptors and exert their effect on cultured astrocytes at concentrations similar to those used clinically, a substantial difference from their effect on SERT. We have demonstrated up-regulation and editing of astrocytic genes for ADAR2, the kainate receptor GluK2, cPLA2 and the 5-HT2B receptor itself after chronic treatment of cultures, which do not express SERT and after treatment of mice (expressing SERT) for 2 weeks with fluoxetine, followed by isolation of astrocytic and neuronal cell fractionation. Affected genes were identical in both experimental paradigms. Fluoxetine treatment also altered Ca2+ homeostatic cascades, in a specific way that differs from that seen after treatment with the anti-bipolar drugs carbamazepine, lithium, or valproic acid. All changes occurred after a lag period similar to what is seen for fluoxetine’s clinical effects, and some of the genes were altered in the opposite direction by mild chronic inescapable stress, known to cause anhedonia, a component of major depression. In the anhedonic mice these changes were reversed by treatment with SSRIs.
Keywords: gene expression